The Remote Completion Rate of Electronic Patient-Reported Outcome Forms Before Scheduled Clinic Visits—A Proof-of-Concept Study Using Patient-Reported Outcome Measurement Information System Computer Adaptive Test Questionnaires. (October 2019) - Borowsky, Peter A.; Kadri, Omar M.; Meldau, Jason E.; Blanchett, Jacob; Makhni, Eric C.
Abstract : Introduction: Patient-Reported Outcome Measurement Information System (PROMIS) questionnaires are amenable to remote administration. This study sought to determine remote completion rates of PROMIS questionnaires before clinic visits. Methods: Patients were e-mailed a set of PROMIS forms. Completion rates were analyzed by visit type, provider seen, and patient demographics. Results: Seven hundred forty total appointments were included. Sixty-seven percent of encounters had previsit form completion. High completion rates were found for all visit types (74%, 67%, and 64% for new, return, and postoperative visits, respectively). Women had a higher completion rate than men (71% versus 64%; P = 0.031). White patients (72%; P = 0.001) and patients in the third median household income quartile ($53, 725 to $83, 088; 72%; P = 0.008) had higher completion rates than their respective counterparts. Conclusion: Most patients remotely completed PROMIS forms. The efficiency and accessibility of PROMIS forms may help improve ease of collection of patient-reported outcomes.